2008
DOI: 10.1021/jp8057417
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Barrier Height for Acetyl Radical Dissociation from Acetyl Chloride Photodissociation at 235 nm Using Velocity Map Imaging

Abstract: This work uses velocity map imaging to determine the barrier height for acetyl radical, CH 3 CO, dissociation to CH 3 + CO. Photodissociation of acetyl chloride at 235 nm generates acetyl radicals with an internal energy distribution spanning this barrier. We determine the velocity and internal energy distribution of all nascent acetyl radicals, stable and unstable, by measuring the velocities of the Cl( 2 P 3/2 ) and Cl( 2 P 1/2 ) cofragments. These Cl cofragments are detected with 2 + 1 resonance-enhanced mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 43 publications
1
26
0
Order By: Relevance
“…It has been shown that VMI is applicable to reactive intermediates that are only available in small number densities. [35][36][37][38] Excited-state computations of the larger alkyl radicals are on the other hand still scarce and only vertical excitation energies have been calculated for a number of alkyl radicals. 39 Complete active space self-consistent field (CASSCF) computations on t-butyl suggested that in addition to the C-H coordinate, the C-C coordinate might be relevant in the photodissociation of alkyl radicals.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that VMI is applicable to reactive intermediates that are only available in small number densities. [35][36][37][38] Excited-state computations of the larger alkyl radicals are on the other hand still scarce and only vertical excitation energies have been calculated for a number of alkyl radicals. 39 Complete active space self-consistent field (CASSCF) computations on t-butyl suggested that in addition to the C-H coordinate, the C-C coordinate might be relevant in the photodissociation of alkyl radicals.…”
Section: Introductionmentioning
confidence: 99%
“…D 0 (C-Cl) is the bond dissociation energy of the C-Cl bond, experimentally determined as 83.62 ( 0.15 kcal/mol, 24,25 which is quite close to the theoretical value calculated at the UCCSD(T)/CBS//UCCSD(T)/aug-cc-pVTZ level of theory as 83.4 kcal/mol. 13 It is slightly higher than the G4//B3LYP/6-311++G(3df,2p) value of 82.57 kcal/mol. 26 Figure 1.…”
Section: Previous Experimental Resultsmentioning
confidence: 70%
“…The details of this apparatus and the experimental results are described elsewhere. 1,13 In short, a supersonic molecular beam of acetyl chloride molecules was photodissociated at 235 nm, and the Cl and CH 3 CO cofragments were photoionized and detected with velocity map imaging to measure the distributions of velocities, P Cl (υ) and P acetyl (υ) respectively. The acetyl radicals were produced in a range of velocities corresponding to internal energies that span the barrier to further dissociation.…”
Section: Previous Experimental Resultsmentioning
confidence: 99%
“…Many works have been published on this process, the products of which are associated with tautomerization to the keto isomer followed by rapid preferential cleavage of the newly formed C–C bond to yield methyl radicals and the acetyl cation. The acetyl cation would be expected to yield the highly unstable acetyl radical on neutralization and subsequently to decompose very rapidly to methyl radicals and CO in our apparatus. As these are the same products as our primary ‘keto cation’ decomposition, it is not expected that we would observe any new species that grow in at the expense of secondary ionization of 1‐propen‐2‐ol with ionization current increases.…”
Section: Discussionmentioning
confidence: 99%